Edward R. Murrow and Fred Friendly, President of CBS News (Tufts Archival Research Center, 2005)
7x9. Photo undated, approximate. Caption on back: "President of CBS News, Fred W. Friendly, produced the radio program Hear It Now and the television program See It Now with Murrow."